2018 Global food policy report: Regional developments: Central Asia - Akramov, Kamiljon T.; Ilyasov, Jarilkasin; Park, Allen (International Food Policy Research Institute, 2018)
After experiencing significant negative external shocks beginning in late 2014, the Central Asian countries—Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan—began to enjoy more favorable external economic conditions in late 2016. Improvements include considerable increases in nonrenewable commodity prices and economic recovery in the region’s key trading partners, including resumption of growth in Russia, a key driver of remittance flows and trade for Central Asian economies.1 These favorable external factors increase economic activity and food security in Central Asia through their impact on export earnings, remittance flows, and investments from the region’s main economic partners.